Phenomenology of scotogenic scalar dark matter - Ávila, Ivania M.; De Romeri, Valentina; Duarte, Laura [UNESP]; Valle, José W. F. (Springer Nature, 2020)
We reexamine the minimal Singlet + Triplet Scotogenic Model, where dark matter is the mediator of neutrino mass generation. We assume it to be a scalar WIMP, whose stability follows from the same Z2 symmetry that leads to the radiative origin of neutrino masses. The scheme is the minimal one that allows for solar and atmospheric mass scales to be generated. We perform a full numerical analysis of the signatures expected at dark matter as well as collider experiments. We identify parameter regions where dark matter predictions agree with theoretical and experimental constraints, such as neutrino oscillations, Higgs data, dark matter relic abundance and direct detection searches. We also present forecasts for near future direct and indirect detection experiments. These will further probe the parameter space. Finally, we explore collider signatures associated with the mono-jet channel at the LHC, highlighting the existence of a viable light dark matter mass range.